Molecular basis of ciprofloxacin (fluoroquinolone)-resistant in clinical isolates of Escherichia coli - Ahmed Mohammed Tofiq (Zanco Journal of Pure and Applied Sciences, 2020)
It has recently been shown that antibiotic resistance is considered as one of the extremely imperative worrisome in medicine, with tremendously resistant pathogens of numerous species of bacteria demonstrating difficult to treat. The aim of this study was to determine mutations in DNA gyrase subunits GyrA and GyrB, and topoisomerase IV subunits ParC and ParE in clinical isolates of Escherichia coli, which are important determining factors for paramount levels of fluoroquinolone (ciprofloxacin) resistance. This article was achieved through five months survey for the occurrence of ciprofloxacin resistant E. coli in clinical samples from outpatient clinics in Kalar city. Fifty seven samples were collected included (4) wound swabs, (1) conjunctiva, (2) vaginal and (2) otitis media swabs, as well as (48) urine samples from the period March to August, 2018. The collected samples were cultivated on selective and differential media for E. coli isolation. Classical biochemical tests and molecular basis (16SrRNA) were performed for the identification of 14 isolates of E. coli. These isolates were tested for antibiotic sensitivity (17 different antimicrobials agents were tested, included ciprofloxacin). The isolates showed ciprofloxacin resistance and were checked for mutations in the quinolone resistance-determining regions (QRDR) of gyrA, gyrB, parC, and parE genes by polymerase chain reaction and DNA sequencing. Subsequently, amino acid substitutions were detected by Clustal Omega. Two main mutations in gyrA, in addition to a range of extra mutations, were identified in resistant isolates. There were no mutations in the QRDR of each of gyrB, and parC of CIP-resistant isolates, except a single mutation in gyrB out of QRDR, and only in one isolate. However, one main mutation in parE, as well as two extra mutations were identified in two resistant isolates. The current study has demonstrated the occurrence of CIP-resistant E. coli in clinical specimens, with half of them being unsusceptible to ciprofloxacin, among those, 85.7% were also resistant to at least three antibacterial classes.